SISTEM INFORMASI ALAT KESEHATAN BERBASIS WEB - Arianto Pradana Arianto Pradana; Ibnu Hardi Ibnu Hardi (Jurnal Ilmiah Sistem Informasi, 2022)
The use of computer technology in various business fields has become a necessity, especially in the current era of globalization, where information around the world can be obtained quickly. The increasing need for information, especially for medical devices, not all areas exist, even if most of them are in big cities, getting customer remote information takes a long time and customers want to do work quickly so that all work can be completed in the least possible time. The use of computer technology is more likely to meet the information needs of customers. Medical device information system at PT. MERAPI UTAMA PHARMA Semarang based on the web is expected to be useful, because with the information via the web like this, customers can place orders remotely and know the amount of stock available so they do not have to come directly to PT. MERAPI UTAMA PHARMA which can take a long time, and by using the web makes it easier for customers to place orders quickly by minimizing the risk of errors in writing item codes.